2018
DOI: 10.1002/jobm.201700663
|View full text |Cite
|
Sign up to set email alerts
|

The first Taxus rhizosphere microbiome revealed by shotgun metagenomic sequencing

Abstract: In the present study, the shotgun high throughput metagenomic sequencing was implemented to globally capture the features of Taxus rhizosphere microbiome. Total reads could be assigned to 6925 species belonging to 113 bacteria phyla and 301 species of nine fungi phyla. For archaea and virus, 263 and 134 species were for the first time identified, respectively. More than 720,000 Unigenes were identified by clean reads assembly. The top five assigned phyla were Actinobacteria (363,941 Unigenes), Proteobacteria (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…The same study showed, that genes involved in the transformation and degradation of organic pollutants are also mostly present in plasmids [24]. Such knowledge has already been applied, and plasmids with genes responsible for toluene degradation were successfully transferred to aerial plant endophytes and increased the total degradation of contaminant that would have been volatilized [26]. Besides, metagenomic research performed in changing environmental conditions showed that the microbial communities in terms of its genetic and taxonomic composition could be linked to its activity to metabolize carbon.…”
Section: Metagenomic Approach To Enhance Phytoremediation Efficiencymentioning
confidence: 90%
See 3 more Smart Citations
“…The same study showed, that genes involved in the transformation and degradation of organic pollutants are also mostly present in plasmids [24]. Such knowledge has already been applied, and plasmids with genes responsible for toluene degradation were successfully transferred to aerial plant endophytes and increased the total degradation of contaminant that would have been volatilized [26]. Besides, metagenomic research performed in changing environmental conditions showed that the microbial communities in terms of its genetic and taxonomic composition could be linked to its activity to metabolize carbon.…”
Section: Metagenomic Approach To Enhance Phytoremediation Efficiencymentioning
confidence: 90%
“…For example, experiment from 2012 showed, that exudate produced by wild rye exposed to hydrocarbons were not as repressive as exudate from wild rye grown on an uncontaminated medium, which overall demonstrated that plants might alter the extent to which they will promote total rhizosphere biodegradation [25]. Thus, it has to be taken into consideration that the overall degree to which plants can exert control over bacterial and fungi communities strictly depends on the concentration of given contaminant and its overall severity of toxic effects [26].…”
Section: Metagenomic Approach To Enhance Phytoremediation Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the PCR bias cannot be avoided and the information about microbial function is not provided. The shotgun metagenomic sequencing (Hao et al, 2018b), complementary to the amplicon sequencing, could more objectively reflect the microbiome status quo and dynamics of anode biofilm, and should be utilized in the future study.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%